MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL LEARNING CYCLE 7E PADA SISWA KELAS III SDN CIPETE SELATAN 03 - Nurrohmah Safitri; Tunjungsari Sekaringtyas; Prayuningtyas Angger Wardhani (STKIP Subang, 2025)
This Classroom Action Research aims to improve the science learning outcomes of third-grade students through the implementation of the 7E Learning Cycle model. The study was conducted at SDN Cipete Selatan 03 with a total of 31 third-grade students in the 2025/2026 academic year as research subjects. The classroom action research model employed in this study refers to the Kemmis and McTaggart spiral design. The results showed that students’ science learning outcomes in Cycle I reached 65%, and increased in Cycle II to 87%, thereby meeting the predetermined success criteria. Based on these findings, it can be concluded that the application of the 7E Learning Cycle model effectively improves the science learning outcomes of third-grade students. Therefore, the 7E Learning Cycle model is recommended as an alternative instructional approach that teachers can use to enhance students’ learning outcomes in science.